Vliv provedení zateplení objektu penzionu na výdaje spojené s provozem této nemovitosti. - Mach, Stanislav (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2015)
Diplomová práce řeší stavbu penzionu a zabývá se posouzením vlivu zateplení na výdaje spojené s provozem této nemovitosti. Penzion se nachází na ulici Valtická v Mikulově. Objekt má jedno nadzemní podlaží a je založen na základových pasech. Zastřešení penzionu je řešeno nepravidelnou sedlovou střechou. V první části diplomové práce je v teoretickém úvodu je zmíněna možnost zateplení staveb a způsoby zateplení. V praktické části diplomové práce je provedeno posouzení součinitele prostupu tepla penzionu a náklady spojené s vytápěním. Je zde i návrh obměny obvodové konstrukce s posouzením součinitele tepla a jsou zde i navrženy úpravy k snížení nákladů na provoz nemovitosti.

The thesis solves the construction of the pension and deals with the assessment of the impact of the thermal insulation on expenses related to the operation of the property. The pension is situated on the street Valtická in Mikulov. The building has one floor and is founded on strip foundations. Roofing of the house is solved with irregular gable roof. In the first part of the thesis is a theoretical introduction mentions the possibility of building insulation and insulation methods. In the practical part of the thesis is an assessment of the heat transfer coefficient of the pension and costs associated with heating. There is also a proposal for modifications of the envelope construction with assessment of the heat factor and there are also proposed modifications to reduce the costs of operating the property.
Influence of insulation of a guest house on expenses related to the operation of the property
Keywords: penzion; zateplení; základový pas; nepodsklepený objekt; ubytovací služby; energetická náročnost budov; ENB; návratnost investice; úspora energie; prostup tepla; pension; insulation; strip foundation; slab building; accommodation services; energy performance of buildings; ENB; return on investment; saving energy; heat transmission